Memórias acadêmicas e o processo de formação ressignificando minhas práticas pedagógicas - CRUZ, Diana Nascimento da (2024)
This work has as reason to elaborate a memorial of teacher education addressing relevant points of the student, professional and academic life history of Diana Nascimento da Cruz, with the purpose of describing memories from the first contacts of the school life, professional and from the beginning of my entrance in the course of Full Degree in Pedagogy, offered by the National Plan for the Training of Basic Education Teachers- PARFOR, at the University Campus of Abaetetuba of the Federal University of Pará. Reflects my changes, mainly in my pedagogical practices, with the knowledge acdquired during the period of teacher education, in the face of a new understanding of pedagogical theories and educational conceptions. In this sense, the conclusion of the Pedagogy course contributed to the acquisition of the multidimensional understanding of education.